Pizzasaurus Rex - Wagner, Justin (Oni Press, 2018)
Today, Jeremy Duderman, the most awesome scientist of his generation--who only goes unnoticed because everyone keeps bullying him--is ready to step into the spotlight. He has invented the Reality Alternative Dimensionator, "R.A.D.," and rex Raditude, the Pizzasaurus, has used it to enter our dimension. Unfortunately, Emperor Buzzkill and his horde of minions have followed, and only Jeremy can help Rex defeat them.